Effects of EDM parameters on residual stress and microhardness in Al-10 %SiCmicro-SiCnano hybrid composites: A Simulation and Experimental study - Umair Arif; Imtiaz ali Khan; Faisal Hasan; Afsar Husain; Sanan H. Khan (Results in Engineering)
The study was conducted in two parts. In the first part, a thermo-mechanical model was developed using Ansys software to predict the residual stresses generated in Al-SiC-based hybrid composites after Electrical Discharge Machining (EDM). The simulation results were validated through experiments. The process parameters used in both simulations and experiments included three different values of I, Ton, and the percentage of nano-SiC particles in Al-10 %SiCmicro-SiCnano-based hybrid composites. A Taguchi L9 orthogonal array was employed as the design of experiments. Residual stresses were experimentally measured using X-ray diffraction (XRD). The simulations indicated the formation of compressive residual stresses in the hybrid composites in machined area and tensile residual stresses away from it.. XRD measurements also revealed that while tensile stresses predominated, compressive stresses were also observed in certain cases. The peak value of 327 MPa stress was observed in Al-10 %SiCmicro-3 %SiCnano hybrid composite at 10Amp I and 418 µs Ton. The second part of the study focused on a parametric analysis of the experimental results. The performance parameters considered were residual stresses and microhardness. The ANOVA results highlighted that pulse-on time had a significant impact on microhardness. %SiC nano was the highest contributing factor to stress (33.20 %) and Ton was the highest contributing factor for microhardness (26.74 %). Main effect plot depicted that maximum stress was observed at 3 % SiC nano particles, 204 µs Ton and 6 A I, and microhardness was observed at 4.5 % SiC nano particles, 204 µs Ton and 6-A I. Surface plot depicts that maximum residual stress was observed at 3 % SiC nano content and 10-A I, at 3 % SiC nano content and 204 µs Ton and at 10-A I and 204 µs Ton. Fuzzy TOPSIS analysis identified an optimal combination of parameters: Al-10 %SiCmicro-4.5 %SiCnano composition, 10 A I, and 204 µs Ton. A notable trend was observed in most workpieces: the microhardness of the material decreased after EDM, primarily due to the development of microcracks on the composite surface, which led to material softening. Interestingly, in cases where residual stresses were maximized, the reduction in microhardness was minimal. This suggests that the induced stresses contributed to strain hardening in the hybrid composites.